THE EFFECT OF THE TEAM ASSISTED INDIVIDUALLY (TAI) LEARNING MODEL ON THE ABILITY TO UNDERSTAND MATHEMATICAL CONCEPTS - Ndruru, Firman Emanuel (Afore : Jurnal Pendidikan Matematika, 2022)
This study aims: to determine the effect of the Team Assisted Individual learning model on understanding mathematical concepts. This type of research is quasi-experimental research. The population in this study were all students of class VIII. The research sample consisted of two classes, namely class VIII-A as the experimental class and class VIII-B as the control class. Collecting data using tests to measure student learning outcomes. The design of this study used the Matching Pretest-Posttest Control Group Design with the initial condition that the student learning outcomes (pretest) were balanced. The research findings show that (1) the material model of the SYSTEM of Linear Equations of Two Variables (2) the Team Assisted Individually Learning Model supports students in discovering mathematical concepts based on student learning outcomes that the Team Assisted Individually model influences the ability to understand concepts. So the Team Assisted Individually learning model is a learning model that can adapt to individual differences and is related to student achievement motivation. Suggestions from researchers, the Team Assisted Individually learning model can be used as a reference in improving student learning outcomes because it can make students active and creative.